A Pair Of Twins - Kavitha Mandana (Karadi Tales Company Pvt. Ltd, 2014)
Lakshmi and Sundari are an unusual pair of twins with an unusual connection . . . But not everyone knows how special they are until they're both called upon to save the day. Kavitha Mandana tells this story with brilliance and warmth, while Nayantara Surendranath lends vibrancy to it with her magnificent artwork.